From value recognition to effective implementation: the main problems and strengthening paths of law enforcement to combat IUU fishing - Linlin Chen; Yuejun He (Frontiers in Marine Science)
As a cornerstone institutional arrangement for marine fishery resource conservation, the legal efficacy of IUU fishing prohibitions is fundamentally contingent upon the standardized enforcement capacities of fishery law enforcement personnel. This study investigates the institutional disjuncture between statutory prohibitions against illegal fishing and their practical implementation. Empirical evidence derived from 526 structured questionnaires and 195(37.1% of the 526) in-depth interviews with enforcement officers across four coastal provinces(Nearly 30% of coastal provinces in China)reveals structural contradictions within the current enforcement framework: On the one hand, cognitive dissonance regarding the ecological value of fishing bans among certain officers has precipitated deficient value internalization. On the other, skepticism about the legitimacy of legal norms has engendered multiple enforcement anomalies—including but not limited to selective enforcement, passive evidence collection, sentencing disparity, and administrative-criminal procedure linkage barriers. These institutional implementation defects substantially constrain marine ecological governance efficacy. To address this institutional predicament, a systematic governance framework is proposed: Value dimension : Establish sustainable value-shaping mechanisms through capacity-building programs to foster long-term ecological consciousness; Regulatory dimension : Develop precision-engineered administrative-criminal linkage protocols to ensure coherent legal implementation; Operational dimension : Forge a three-dimensional governance architecture integrating administrative enforcement, criminal justice, and public interest litigation to construct a comprehensive “administrative-criminal-civil” liability regime. Through synergistic advancement in value recognition reconstruction, regulatory execution reinforcement, and innovative governance practices, this tripartite approach projects to enhance IUU fishing enforcement efficacy, thereby institutionalizing sustainable utilization of marine fishery resources.